Catalogue of the Pyrrhocoroidea (Hemiptera: Heteroptera) from Argentina - Melo, María Cecilia (2013)
The superfamily Pyrrhocoroidea from Argentina is catalogued. The included families, Pyrrhocoridae and Largidae, represent a total of 22 species. For each of them we include all the bibliographic references with the locality data and host plants, and new records from material studied at the Museo de La Plata collection; the type species of each genus is also mentioned. Maps and a table with the host plants arranged in families are also included.